Evaluative Knowledge and Skills of Student Teachers Within the Adapted Degree Courses - Agrati, Laura Sara; Vinci, Viviana (Frontiers in Education, 2022)
Due to the COVID-19 pandemic, many university initial teacher education courses have been adapted into remote mode. Starting from specific topics of the training curriculum, the work focuses on adapting courses on evaluative knowledge and skills in an e-learning environment; it examined the development of student teachers' evaluative knowledge (terminology and concepts) and skills (design of paper and pencil assessment tools) who took the adapted courses. A comparative study of two adapted university degree courses (University of Bergamo and Mediterranean University of Reggio Calabria in Italy - initial training of future primary school teachers) in the area of evaluation, was carried out. The study involved 155 primary school student teachers and made a mixed method investigation with sequential system. The first exploratory method collected quantitative data by an ‘ad hoc’ questionnaire on student teacher’ knowledge, the second confirmatory method gained qualitative data through the document analysis of paper-and-pencil assessment tool on student teachers’ skill. The results highlight substantial similarities on knowledge (function of evaluation, difference between evaluation and assessment, object of school evaluation) and skill (ability to refer to real situations and promote situated knowledge) but also differences (construct of school 'evaluation processes' and ability to provide different solutions for solving the task) e specific difficulty in implementing the 'constructive alignment'. Contribution to the field The investigation experience is functional to training future teachers capable of taking an active role and reflecting on their learning in a meaningful and engaging way, in the development of future personal and professional life. In the perspective of new teaching technologies potentialities, research shows the importance of adapting a university course remotely through careful planning of the learning environment and the targeted use of online technologies and resources, in order to support evaluation knowledge and skills.